ANALISIS PERENCANAAN DAN EVALUASI PUBLIC RELATIONS PROGRAM GERAKAN SEDEKAH SAMPAH DI KAMPUNG KEDAUNG WETAN - Afni Yoana; Afrit Wira Buana; Rahmat Mulyana (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2020)
The Alms Trash Program was launched to increase the role of active communities, create awareness of environmental involvement, and build a new culture of collecting waste. The communication and message delivery program is carried out through a socialization program and learning presence by giving alms. This study aims to understand the PR process (Public Relations) which consists of gathering facts and formulating problems, planning and programming, actions and communication, and evaluating the alms program conducted by the organizer. The research method used is a case study research method. Collecting data through interviews, observations, and documents. The collection of facts carried out by the supervisor starts with comments and complaints submitted by external parties, also goes to the field to see firsthand the environmental conditions of the City of Tangerang. Program organizers, licensed, designed, goal setting, audience resolution, media selection and public relations techniques, and budget planning. The action taken by the organizer in the waste alms program is.